Factors associated with quality of life in cancer patients at a social security pain therapy unit: Factores asociados a la calidad de vida en pacientes con cáncer en una unidad de terapia del dolor de la seguridad social - Pacheco-Feijoó, Gloria (2023)
Introduction: Quality of life is one of the main concerns for cancer patients in palliative care; however, studies on quality of life in these patients are limited. Objective: To determine the factors associated with quality of life in patients with oncological disease in palliative care. Methods: Observational, analytical study in 184 cancer patients treated in a Pain and Palliative Care Unit during 2021. The dependent variable was quality of life; independent variables were age, sex, education level, occupation, oncological diagnosis, disease duration, and stage. Crude (RP) and adjusted (aRP) prevalence ratios were calculated with a 95% confidence level. Results: The median age was 63 years, and 66.3% were female. Factors associated with quality of life were breast cancer (aRP=1.21; 95% CI: 1.07-1.36; p!<0.010), prostate cancer (aRP=1.36; 95% CI: 1.18-1.56; p!<0.010), or multiple myeloma (aRP=1.33; 95% CI: 1.15-1.53; p!<0.010), compared to other cancers such as Hodgkin's lymphoma, stomach, kidney, or pancreatic cancer; disease duration longer than 36 months (aRP=1.13; 95% CI: 1.01-1.27; p=0.040), and stage III (aRP=1.30; 95% CI: 1.19-1.42; p!<0.010) were also associated with quality of life. Conclusions: Factors associated with quality of life were having breast, prostate, or multiple myeloma cancer, compared to having another type of cancer; in addition to a disease duration longer than 36 months and stage III compared to stage I/II.